Metabolic Demands, Center of Mass Movement and Fractional Utilization of V˙O2max in Elite Adolescent Tennis Players During On-Court Drills - Björklund, Glenn; Swarén, Mikael; Norman, Magnus; Alonso, Juan; Johansson, Fredrik (Frontiers in Sports and Active Living, 2020)
The aim of the study was to investigate the exercise intensity and energy expenditure during four types of on-court tennis drills. Five female and five male tennis players participated in the study (age: 17±2 years; V ̇O_2max: 54±6 ml·kg-1·min-1). Anthropometric measures were taken for each player and, on separate days, each player performed i) treadmill running to determine V ̇O_2max and ii) four different tennis drills (Drill1-4) during which V ̇O_2, blood lactate concentration, ratings of perceived exertion (RPE 6-20) and displacement of centre of mass (m) using 3D kinematics were recorded. The drills were designed to simulate match play with 90 s of rest between each drill. A repeated two-way ANOVA was used for physiological and biomechanical data and Friedman’s test for RPE using < α 0.05. Fractional utilisation of V ̇O_2max was greatest during Drill1 81.8±7.0 % and lowest during Drill4 72.4±5.2 % (p<0.001) with no difference between sexes (p>0.05). The highest energy expenditure was during Drill1 and lowest during Drill4 (77±15 kcal and 49±11 kcal respectively, p<0.05). Energy expenditure per meter for Drill1-Drill4 was subsequently reduced for each drill with 10.5±2.1, 9.9±2.2, 7.6±1.7 and 8.0±1.6 J·kg-1·m-1 (p<0.01). There were no interaction effects for any of these variables. RPE (6-20) and blood lactate concentration post Drill1-Drill4 were 17.5, 15.5 and 13.0 (overall, legs and arms, p<0.001) and 5.9±2.0, 4.9±1.9, 5.6±2.0 and 5.0±2.2 mmol·l-1 (p<0.05). The findings of this study demonstrate that the on-court tennis drills performed here are suitable for high intensity training in junior tennis players. The energy expenditure per minute is comparable to similar sports whereas the energy expenditure per meter is notably greater.